Gender Differential Prevalence of Overweight and Obesity, Hypertension and Diabetes in South India: A Population-Based Cross-Sectional Study - Mohanraj Sundaresan; Ganesan Velmurugan; Mani Dhivakar; Arulraj Ramakrishnan; Mathew Cherian; Thomas Alexander; Krishnan Swaminathan (Ubiquity Press, 2024)
Background: India is facing triple epidemic of Non communicable diseases (NCDs) including high body mass index (BMI), high blood pressure and high blood glucose, contributing to more than half of deaths of all mortality, however, information in different demographics is limited, especially, in India. The aim of the study is to compare the prevalence of overweight, obesity, hypertension, and diabetes, along with the occurrence of multi-morbidity, across gender-specific populations in rural, suburban, and urban regions of India. Methods: This was a cross-sectional, population-based study including adults aged 20 and above in rural, suburban, and urban areas near Coimbatore, India. All participants were interviewed using a detailed questionnaire and had their anthropometric measurements, including height, weight, blood pressure, and blood samples collected. Gender specific and location specific prevalence of overweight, obesity, hypertension, diabetes, and multimorbidity were assessed. Results: This study included 2976 individuals, of which 865 were from rural areas, 1030 from sub-urban areas, and 1081 from metropolitan areas. The mean systolic and diastolic blood pressure were higher in rural participants than in sub-urban and urban participants, despite the fact that the prevalence of hypertension was higher in sub-urban (47.1%) than in rural (36.4%) and urban (39.7%, p < 0.001). In sub-group analysis, sub-urban areas had a greater prevalence of hypertension in both men and women (53.5% and 41.7%, p < 0.001) than rural areas (41.9% and 31.3%, p = 0.001) or urban areas (45.9% and 35.5%, p < 0.001). Compared to rural (16.1%) and urban (23%), sub-urban areas had a greater prevalence of diabetes (25.8%, p < 0.001). Urban residents (47.5%) had higher rates of overweight and obesity than rural (31.4%) and sub-urban (34.1%, p < 0.001) residents. The association between diabetes and hypertension was present in the unadjusted model and persisted even after age and BMI adjustments. Though not in men, higher levels of education were associated to a higher prevalence of diabetes in women. Diabetes was associated to being overweight or obese in women, however this association was significantly reduced once BMI was taken into account. The overall multimorbidity was 3.8%, however, women had a higher overlapping prevalence (2.8%) compared to men (1%, p < 0.001). Conclusions: Diabetes and hypertension were prevalent comorbidities across all demographics, with higher rates in suburban and urban areas. Women exhibited higher rates of multimorbidity than men, regardless of the demographic area.